Self-regulatory practices of electronic trade and transnational public order in the context of ensuring the economic security of the state - HONCHARENKO, Olena; Mariia POZHYDAIEVA; Larysa NESKORODZHENA; Oleksandra KOLOHOIDA (Revista Jurídica Portucalense, 2024)
This article studies the positive and negative aspects of self-regulation in electronic trade through a thorough study of factors that may include: the legislative framework (state policy, legal norms), the organization of electronic trade control means (both by the state and by consumer organizations and self-regulatory organizations), the practice of traders in a particular market, the honesty of sellers, the ethics of carrying out electronic trade, consumer considerations (vision, interests), and martial law conditions. All of this has an overall impact on the economic security of the state. Today, issues related to self-regulatory practices of electronic trade pose fundamental challenges for a stable, predictable and secure electronic trading space in the context of strengthening the economic security of the state. It is argued that the level of national economic security can be measured both by compliance with the mandatory provisions of transnational and national public order and by the benefits of self-regulatory practices of electronic commerce. In the context of war, self-regulation of electronic trade requires its implementation on the ethical basis of preserving human life and prohibiting cooperation with counterparties from the aggressor State.